The genetics of the mimetic coloration in the Butterfly Heliconius cydno weymeri (1996)
The genetic bases of the wing color pattern in the neotropical butterfly Heliconius cydno weymeri were investigated. Evidence from F1 broods of wild-caught females indicates that the studied subspecies is composed of two mimetic forms, weymeri and gustavi, which differ mainly by single allele substitution of major phenotypic effect. Three additional Mendelian genes are hypothesized to possess alleles that contribute to Müllerian mimicry with two alternative model species (mimicked by the two mentioned polymorphic forms), and a fifth one is hypothesized to possess alleles that are mimetically irrelevant. Segregation occurred at all five putative loci. Most of the broods show ratios consistent with simple Mendelian segregation. Broods inconsistent with simple Mendelian inheritance can be explained by (1) a possible epistatic interaction between some of the hypothesized loci and/or the modifier effect of two addtional genes; and (2) a possible effect of sex on the expression of one of the hypothesized loci. There is evidence that the genetic system has evolved epistatic interactions in order to facilitate mimetic resemblance. There is no evidence of linkage between mimetically relevant loci except for one pair of these. This is the first report on the genetic bases of the wing color pattern variation of the species Heliconius cydno.